Monetary Policy and Macroprudential Regulation with Financial Frictions - Agénor, Pierre-Richard, author (Cambridge, Massachusetts : The MIT Press, 2020)
A monograph that accounts for financial frictions in some of the most-used macroeconomic models. An attempt to bring practical reality into macroeconomic theory
Keywords: Monetary policy--Econometric models; Macroeconomics